Exploring Denosumab’s potential in aneurysmal bone cyst treatment: A scoping review - Vinesh Sandhu; Vivek Ajit Singh; Ajay Puri (Journal of Orthopaedic Surgery)
Background: Denosumab effectively treats RANKL-mediated bone disorders by inhibiting osteoclast activity. While approved for giant cell tumours, its role in aneurysmal bone cysts (ABC) remains unclear. This review explores denosumab’s application in ABCs, focusing on its role, outcomes, and adverse effects. Methods: A scoping review adhering to PRISMA Extension for Scoping Reviews guidelines was conducted. The search involved five databases from inception until 31 December 2023. Results: From an initial 390 studies, 29 were selected post-screening involving 67 patients. The most common ABC sites were the spine ( n = 42) and pelvis ( n = 7). Denosumab served as primary treatment in 25 patients (37.3%), neoadjuvant in 11 (16.4%), second-line therapies after inadequate initial therapies in 24 (35.8%), and adjunct therapy in seven cases. All patients demonstrated favourable clinical and radiological responses post-denosumab. 10 patients (15%) experienced tumour recurrences: six after denosumab discontinuation (3-17 months post-cessation), three post-surgery following neoadjuvant denosumab, and one during ongoing treatment. Adverse effects reported were hypocalcaemia ( n = 10), hypercalcemia ( n = 14), and sclerotic metaphyseal bands ( n = 2), all in the paediatric age group. While hypocalcaemia surfaced early in denosumab therapy, hypercalcaemia manifested 2.5-6 months post-discontinuation, mainly managed with bisphosphonates. Fewer than half of the studies had follow-ups that exceeded 2 years. Conclusion: Denosumab may be an effective therapy for ABC, especially for high-risk cases like spinal and pelvic tumours. It can also be utilized as a second-line for recurrence/failed initial intervention or as neoadjuvant therapy. Concerns exist about tumour recurrence and rebound hypercalcemia, necessitating careful monitoring, longer follow-up, and prophylactic measures. Prospective clinical trials are warranted for deeper insights.